2013
DOI: 10.1016/j.fra.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Absence of pyruvate anti-oxidant effect on granulocytes stimulated toll-like receptors

Abstract: a b s t r a c tAim & background: Pyruvate is considered as an anti-inflammatory and anti-oxidant produced from glucose metabolism. We examined the effects of sodium pyruvate on reactive oxygen species (ROS) production induced by opsonized particles in phagocytosing or toll-like receptor 4 (TLR4)-stimulated granulocytes obtained from type 2 diabetic (T2DM) patients compared with those from healthy individuals. Methods: Luminol-dependent chemiluminescence was used to quantify the ROS generated. The phagocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A further possible mechanism to explain these results is that high glucose levels have been associated with low neutrophil chemotactic activity [40, 41] and reduction of the phagocytic activity of polymorphonuclear cells in diabetic patients [42, 43]. Chamon et al[44] showed a 370% and 199% increase in ROS generation during the process of phagocytosis in healthy subjects and DM patients respectively. In the presence of pyruvate, these percentage increases were reduced to 81% and 80%, respectively.…”
Section: 0 Discussionmentioning
confidence: 99%
“…A further possible mechanism to explain these results is that high glucose levels have been associated with low neutrophil chemotactic activity [40, 41] and reduction of the phagocytic activity of polymorphonuclear cells in diabetic patients [42, 43]. Chamon et al[44] showed a 370% and 199% increase in ROS generation during the process of phagocytosis in healthy subjects and DM patients respectively. In the presence of pyruvate, these percentage increases were reduced to 81% and 80%, respectively.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Tyrosine is metabolized to tyramine by gut microbes and is negatively correlated with inflammation biomarkers and cardiometabolic risk factors [49]. Linoleic acid, nicotinate, and nicotinamide metabolism and unsaturated fatty acid biosynthesis are all closely associated with the occurrence and development of diabetes [21,[50][51][52][53]. Notably, Spearman's correlation analysis indicated that Lactobacillus abundance was positively correlated with 3-Ketocholanic acid, indole, oleoylethanolamide, and nicotinamide levels; 3-Ketocholanic acid is a derivative of cholanic acid involved in the pathogenesis of T2DM and insulin resistance [54].…”
Section: Discussionmentioning
confidence: 99%